Synthesis and Characterization of Binary (Ni:Cu) Metal Oxide Thin Film via Sol-Gel Spin Coating Method for Electrochemical Capacitor Application - Gavandi, S. C.; Mahajan, S. S.; Sutrave, D. S. (Journal of Scientific Research, 2025)
In the present work, binary (Ni:Cu) metal oxide electrode material has been synthesized using the sol-gel spin coating technique. NiCuO exhibits cubic crystal structure and porous, rough surface morphology. The binary nickel copper metal oxide electrode shows a maximum specific capacitance of 781 F/g measured in KOH electrolyte at a scan rate of 5 mVs-1. From the discharging curve, a maximum specific capacitance of 248 F/g is obtained at a current density of 1 mA/cm2. Additionally, the NiCuO electrode has a power density of 206 KW/kg and an energy density of 21 Wh/kg at 1 mA/cm2 with 73 % efficiency. Because of its hydrophilicity and porous agglomerated surface, binary (Ni:Cu) metal oxide is a suitable electrode material for Supercapacitor application.